Optimizing the Gakkum Unit of the Sragen Police Traffic Unit in Handling Over Dimension Over Loading Violations to Realize Traffic Traffic Security - Mahadewa Putra (Tanggon Kosala, 2022)
This research focuses on the optimalization of Traffic Enforcement Unit of Polres Sragen in tackling Over Dimension Over Loading violation in order to create security, safety, order, and smooth traffic. The objective of this research is to understand the management and optimalization method of Traffic Enforcement Unit of Polres Sragen in overcoming Over Dimension Over Loading (ODOL). The concept used are optimalization, Over Dimension Over Loading and Security, safety, order, and smooth traffic. The theory used are SWOT (Strength, Weakness, Opportunity, and Threat) theory analysis, 6M (Man, Money, Materials, Machines, Method, and Market) theory management, and POAC (Planning, Organizing, Actuating, and Controlling) theory management. The method used in this research is qualitative with field type of research. The data is collected through interview, observation, and document study. Interactive model which consists of data reduction, data presentation and conclusion is used as data analysis method. This research is conducted in Polres Sragen, Jawa Tengah. The high number of Over Dimension Over Loading violations in 2022 has disturbed the security, safety, order, and smooth traffic in Sragen. As the stakeholders in road traffic and transportation, the Traffic Enforcement Unit of Polres Sragen is in charge to handle ODOL violations in order to create security, safety, order and smooth traffic. The results of this research shows that the Traffic Enforcement Unit of Polres Sragen has carried out handling the ODOL violations in the jurisdiction of Polres Sragen, but it has not been carried out optimally. Some of the deprivations are lack of competent human resources, inadequate facilities and infrastructure, lack of budget, and method as well as non-optimal management. Therefore, optimalization of Traffic Enforcement Unit of Polres Sragen has to be done in tackling Over Dimension Over Loading. Things that are need to be improved are personnel competency, supporting facility and infrastructure, activity budget, and method of implementing activities according to the guidelines.